Self-rated health does not predict 10-year weight change among middle-aged adults in a longitudinal population study - Jenkins Paul L; Lindvall Kristina; Norberg Margareta; Emmelin Maria; Lönnberg Göran; Nafziger Anne N (BMC, 2011)
Abstract Background There is a worldwide obesity epidemic, but lack of a simple method, applicable for research or clinical use, to identify individuals at high risk of weight gain. Therefore, the relationship of self-rated health and 10-year percent weight change was evaluated to determine if self-rated health would predict weight change. Methods From 1990 to 2008, adults aged 30, 40, 50 and 60 years were invited to health surveys that included self-rated health and measured weight and height. ANOVA was used to evaluate the relationship of 10-year percent weight change and self-rated health. Results The study population consisted of 29,207 participants (46.5% men). There was no relationship between baseline self-rated health and 10-year percent weight change for middle-aged men or women. Conclusions Self-rated health is not able to predict weight change over a 10-year period in this age group.